Electroacupuncture on Baihui (DU20) and Xuehai (SP10) acupoints alleviates psoriatic inflammation by regulating neurotransmitter substance P- Neurokinin-1 receptor signaling - Cong Qi; Fang Feng; JianNing Guo; Yu Liu; XiaoYao Guo; YuJiao Meng; TingTing Di; XueQing Hu; Yazhuo Wang; Ning Zhao; XiaWei Zhang; Yan Wang; et al. (Journal of Traditional and Complementary Medicine, 2024)
Background: At present, acupuncture-related practices have been widely used to treat psoriasis. In our study, we investigated the effect and explored the mechanism of electroacupuncture (EA) on acupoints Baihui (DU20) and Xuehai (SP10) for the treatment of psoriasis. Methods: Imiquimod-induced psoriasis-like mouse model was used in this study. Mice were treated with electroacupuncture at DU20 and SP10 (depth of 2–3 mm, frequency of 2/15 Hz, intensity of 0.5–1.0 mA, 10 min/day). The severity of psoriasis-like lesions for each group was assessed. In addition, histological analysis of the lesions were performed. The levels of inflammatory cytokines were determined using Elisa. The expression levels of Substance P (SP) and NK1R were measured using Western blotting. In addition, NK1R inhibitor was administrated to evaluate the target of electroacupuncture in our mouse model. Results: Electroacupuncture significantly alleviated IMQ-induced skin lesions and epidermal thickness, accompanied with reduced keratinocyte proliferation, CD3+, CD4+, and CD8+ T cells infiltration. The reduced levels of inflammatory cytokines was observed after electroacupuncture treatment. In addition, electroacupuncture inhibited the expression levels of SP and NK1R. NK1R inhibitor could ameliorate lesional symptoms and suppress epidermal thickening and CD3+, CD4+, and CD8 + T cell infiltration. Conclusions: Electroacupuncture relieved psoriasis-like inflammation and T cell infiltration. This therapeutic action was likely mediated by the modulation of Substance P and its receptor NK1R.